Early predictors of discharge to home among severely injured geriatric patients: A single-system retrospective cohort study. (April 2022) - Lai, Krista; Anantha, Ram V; Fawcett, Vanessa; Tsang, Bonnie; Kim, Michael; Widder, Sandy; ,
Background: Injured geriatric patients experience significant functional decline during their hospitalization, limiting their ability to be discharged home which is a valuable outcome among this vulnerable population. We therefore sought to evaluate the clinical characteristics of injured elderly patients managed within our trauma system and identify early predictors for discharge to home. Methods: In this single-system retrospective cohort study, we evaluated significantly injured (Injury Severity Score ≥12) geriatric (age ≥65 y) patients admitted from Northern Alberta between 2011 and 2016. The primary outcome was discharge disposition to home. Data was analyzed with descriptive statistics, and univariable and multivariable logistic regression modelling. P values less than 0.05 were considered statistically significant. Results: We identified 1548 patients with a median age of 77. Falls accounted for 47% of injuries with median injury severity score of 22; 47% of patients were discharged home with a median hospital length of stay of 8 days. All-cause in-hospital mortality was 19%. On multivariable regression, age, injury severity score, heart rate, systolic blood pressure, and Glasgow Coma Score were independent predictors for discharge home, as well as hospital and intensive care unit length of stay. Conclusion: Nearly half of severely injured geriatric trauma patients were discharged home. The identified predictors provide clues to disposition on admission that trauma providers may use to guide in-hospital care planning, disposition planning, and stimulate early goals of care discussions.